Strategi Implementasi Nilai-Nilai Tasawuf dalam Pendidikan Agama Islam untuk Meningkatkan Akhlak dan Spiritualitas - Sanusi, Muhamad Nur Akbar Sanusi (Education Reserach Center, 2025)
This study focuses on formulating a strategy for integrating Sufi (tasawuf) values into the Islamic education curriculum as a response to the growing moral and spiritual concerns among the younger generation in the era of globalization. The waves of modernization and the influence of secularism have led education to emphasize intellectual development, often at the expense of affective and spiritual dimensions. Using a qualitative approach and literature review method, this research develops a conceptual framework based on tazkiyatun nafs (purification of the soul) and tahdzīb al-akhlāq (moral refinement) as the foundation of learning. Core Sufi values such as sincerity (ikhlas), patience (sabr), and asceticism (zuhud) are incorporated through pedagogical methods rooted in role modeling, reflective learning, and the integration of cognitive and affective aspects. The evaluation of implementation is conducted through observation of behavioral changes, attitudinal shifts, and spiritual development among students. The findings indicate that this strategy strengthens holistic character formation and offers a renewed, contextually relevant direction for Islamic education while remaining grounded in fundamental Islamic values.